High immunoproteasome and low constitutive proteasome subunit levels correlate with sensitivity to bortezomib-containing chemotherapy: update from the Children’s Oncology Group AALL1231 trial - Margot S. F. Roeten; Johan van Meerloo; Suzanne N. van Dijk; Zinia Kwidama; Gaye Jenkins; David T. Teachey; Meenakshi Devidas; Mignon L. Loh; Gertjan J. L. Kaspers; Sonja Zweegman; Gerrit Jansen; Terzah M. Horton; et al. (Haematologica)
Not available.